Acquired von Willebrand syndrome associated with plasma cell myeloma – a rare histopathological bone marrow image - Chraszczewska, Maria; Sokół, Kamil; Kuczkiewicz-Siemion, Olga; Prochorec-Sobieszek, Monika; Szumera-Cieækiewicz, Anna (Polish Journal of Pathology, 2019)
Acquired von Willebrand syndrome (AVWS) is a rare bleeding disorder that is associated with a variety of underlying diseases. We report a case of AVWS associated with plasma cell myeloma. The patient was a 57-year-old male with recurrent bleeding symptoms for a few months. Physical examination was normal. Laboratory studies revealed isolated prolongation of the activated partial thromboplastin time. His factor VIII activity, von Willebrand factor (VWF) Ag, and VWF activity were low. Bone marrow aspirate showed diffuse infiltration of atypical plasma cells and erythroid line hyperplasia.